1971
DOI: 10.1063/1.1676785
|View full text |Cite
|
Sign up to set email alerts
|

Infrared and Raman Spectra of Single-Crystal α-Lead Azide

Abstract: The polarized transmission infrared spectra between 400 and 4000 cm-I and the He-Ne laser excited Raman spectra between 30 and 1500 cm-1 of an oriented single crystal of a-lead azide (PbN 6 ), have been measured and the long-wavelength vibrational modes have been assigned by factor-group analysis. The observed splittings are in essential agreement with the reported space group D2h lL Pnma. The Ramanactive lattice modes are observed in the frequency range 30-210 cm-I' The appearance of peaks in the 1330-1360-cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1972
1972
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Therefore, we assigned this mode to NNN symmetric stretch mode. The fundamental ν 1 symmetric stretch vibrations are IR inactive in azides with linear symmetric azide ions, ,,, while they become IR active for these azides possess nonlinear or/and asymmetric azide ions. Therefore, we infer that the azide ions become nonlinear and/or asymmetric starting from 11.7 GPa. This phenomenon was also found in IR study of RbN 3 …”
Section: Resultsmentioning
confidence: 90%
“…Therefore, we assigned this mode to NNN symmetric stretch mode. The fundamental ν 1 symmetric stretch vibrations are IR inactive in azides with linear symmetric azide ions, ,,, while they become IR active for these azides possess nonlinear or/and asymmetric azide ions. Therefore, we infer that the azide ions become nonlinear and/or asymmetric starting from 11.7 GPa. This phenomenon was also found in IR study of RbN 3 …”
Section: Resultsmentioning
confidence: 90%
“…The mode with weak intensity at 1374 cm –1 is assigned to the NNN symmetric stretch mode, labeled as ν sy temporarily, corresponding to the ν 1 ( A 1 g ) mode at 1375 cm –1 (11.9 GPa) in the Raman spectra. The ν sy mode presented as IR-active at this pressure due to the NNN becoming nonlinear/asymmetric upon compression, as is the fact in Ca­(N 3 ) 2 , Ba­(N 3 ) 2 , and Pb­(N 3 ) 2 . In the process of 10.8–14.9 GPa, the relative intensity of C I4 and C I5 is gradually changed accompanied by the overlap and cross of the ν 2 ( A 2 u ) and ν′ 2 ( E u ) modes, indicating the process of the phase transition (γ → δ). Further compression to 16.1 GPa resulted in the disappearance of C I2 and C I3 modes accompanied by the merging of C I4 and C I5 (Figure f).…”
Section: Results and Discussionmentioning
confidence: 81%
“…The structure at 3300 cm-l has been identified l2 as due to fundamental combinations. Of particular interest is a comparison of these data with those obtained by Iqbal et al 14 for oriented single crystals of a-lead azide, Further studies as to the details of the finer structure of the broad ir peaks observed in the doped and undoped films are currently in progress. 18 …”
Section: A Optical Absorption Of Undoped Filmsmentioning
confidence: 90%